Cost-utility analysis of outpatient department based small biopsies for diagnosis of gynecological cancers: a single centre study - Singh, Priyanka (International Journal Of Community Medicine And Public Health, 2025)
Background: The financial toxicity of treating cancer is exorbitant and health insurance schemes such as the Ayushman Bharat Pradhan Mantri Arogya Bima Yojna, have a great impact in mitigating this difficulty. However, package reallocation can be considered for certain surgical procedures that can be performed on an out-patient basis without requirement of admission. This study was conducted with aim of assessing cost-utility of small biopsies compared with the tier 3 to tier 1 package provided in the PMJAY scheme. The study has relevance and significance to the Indian population and similar populations in the low-middle income or even high-income countries, where the public health insurance system is implemented. Methods: This study compares the cost-utility of performing out-patient diagnostic procedures with those performed in the daycare/in-patient setting, with or without utilization of the public health insurance package. The accuracy of the procedure was assessed for biopsies performed on 145 patients evaluated in the out-patient department (OPD) in 2 years. The accuracy of small biopsy in confirmation of diagnosis and its role in decision making was assessed. Results: The study found high accuracy of outpatient procedures in confirmation of diagnosis of gynecological malignancies while being very cost-effective. Conclusions: This analysis concludes that OPD based biopsies or office procedures are very cost-effective and can significantly and positively impact out-of-pocket expenditure for patients seeking cancer treatments, while saving the costs in the insurance scheme packages.